PENGARUH DISIPLIN KERJA, KOMUNIKASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PADA PT. CAPELLA MEDAN DAIHATSU - Andre Fitriano; Angel Miawtanoto; Tri Permata Sari; Herry Yanto (Universitas Methodist Indonesia, 2021)
The purpose of this study was to determine and analyze the influence of work discipline, communication and competence on employee performance at PT. Capella Medan Daihatsu. Researchers took the population in this study as many as 230 employees. The number of samples in this study were 107 employees. The sampling technique used was simple random sampling. The results showed that simultaneously work discipline, communication and competence had a positive and significant effect on employee performance at PT. Capella Medan Daihatsu and partially work discipline, communication and competence had a positive and significant effect on employee performance at PT. Capella Medan. Daihatsu.